Morse Code Receiver On Invisible Light Using Background Subtraction Method - Yuda Irawan; Refni Wahyuni; Herianto Herianto (Journal of Robotics and Control (JRC), 2021)
Morse code is a system of representation of letters, numbers, punctuation marks and signals using a code of dots and lines that are arranged to represent certain characters in the alphabet or certain signals (signs) that are agreed upon for use throughout the world was studied by nilas[1]. This code was coined by Samuel F.B. Morse and Alfred Vail in 1835 was studied by ming[2]. This research aims at how to apply the Background Subtraction method in the design of the morse sign language receiver in the invisible light. Build an Android-based application for recognition of Morse sign language by keeping messages sent using Morse sign language secret through infrared light from the sight of those who can read the message. From the results of the tests that have been carried out, it is concluded that the level of accuracy of testing using the False Match Rate (FMR) obtained a success percentage of 65% from the 26 character data tested. From the 26 character data tested, it was obtained data with the number of characters that were successfully counted correctly, namely 17 characters, while the character data that failed to be counted was 9 characters with a detection result of 26 characters.